Non-contact, 3D magnetic biomanipulation for in vivo and in vitro applications - Sakar, M. S.; Schurle, S.; Erni, S.; Ullrich, F.; Pokki, J.; Frutiger, D. R.; Ergeneman, O.; Kratochvil, B. E.; Nelson, B. J. (2012 International Symposium on Optomechatronic Technologies, ISOT 2012, 2012)
Micro/nano robots have the potential to revolutionize many aspects of medicine. These untethered, wirelessly controlled and powered devices will make existing therapeutic and diagnostic procedures less invasive and will enable new procedures never before possible. Here we present five degree of freedom (5-DOF) wireless control of fully untethered magnetic micro/nano agents (3-DOF position, 2-DOF orientation). We accomplish this level of wireless control with electromagnetic manipulation systems that we call OctoMag and MiniMag. We demonstrate different magnetic control strategies and combination thereof for potential in vivo and in vitro applications. We show that these systems have the potential to be employed for targeted drug delivery and for procedures such as retinal-vein cannulation that require a high degree of dexterity. © 2012 IEEE.
CRIS-Team Scopus Importer:2023-03-21